Ozonation products from trace organic chemicals in municipal wastewater and from metformin: peering through the keyhole with supercritical fluid chromatography-mass spectrometry. (15th May 2021) - Seiwert, Bettina; Nihemaiti, Maolida; Bauer, Coretta; Muschket, Matthias; Sauter, Daniel; Gnirss, Regina; Reemtsma, Thorsten
Highlights: Suspect/non-target screening of ozonated wastewater effluent for ozonation products Supercritical fluid chromatography-SFC vs. reversed-phase liquid chromatography Hydrophilic and small ozonation products are detected by SFC-MS Dual-media filter removes these ozonation products primarily by adsorption Metformin forms some ozonation products that escape from post-treatment Abstract: Ozonation is an important process to further reduce the trace organic chemicals (TrOCs) in treated municipal wastewater before discharge into surface waters, and is expected to form products that are more oxidized and more polar than their parent compounds. Many of these ozonation products (OPs) are biodegradable and thus removed by post-treatment (e.g., aldehydes). Most studies on OPs of TrOCs in wastewater rely on reversed-phase liquid chromatography- mass spectrometry (RPLC-MS), which is not suited for highly polar analytes. In this study, supercritical fluid chromatography combined with high resolution MS (SFC-HRMS) was applied in comparison to the generic RPLC-HRMS to search for OPs in ozonated wastewater treatment plant effluent at pilot-scale. While comparable results were obtained from these two techniques during suspect screenings for known OPs, a total of 23 OPs were only observed by SFC-HRMS via non-targeted screening. Several SFC-only OPs were proposed as the derivatives of methoxymethylmelamines, phenolic sulfates/sulfonates, and metformin; the latter was confirmed by laboratory-scale ozonation experiments. A complete ozonation pathway of metformin, a widespread and extremely hydrophilic TrOC in aquatic environment, was elaborated based on SFC-HRMS analysis. Five of the 10 metformin OPs are reported for the first time in this study. Three different dual-media filters were compared as post-treatments, and a combination of sand/anthracite and fresh post-granular activated carbon proved most effective in OPs removal due to the additional adsorption capacity. However, six SFC-only OPs, two of which originating from metformin, appeared to be persistent during all post-treatments, raising concerns on their occurrence in drinking water sources impacted by wastewater. Graphical Abstract: Image, graphical abstract